2021
DOI: 10.21203/rs.3.rs-829347/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Characteristics and Prognostic Factors of HIV-Positive Patients With Lymphoma in the Poverty Region of China: A Real-World Multicenter Analysis

Abstract: Background: People living with HIV (PLWHIV) are at increased risk of Hodgkin and non-Hodgkin lymphoma compared with HIV-negative individuals. However, high-quality epidemiological data for lymphoma among PLWHIV from low-income and middle-income countries are scarce, especially in South China. This retrospective study aimed to better define the clinical characteristics, outcomes, and prognostic factors of HIV-associated lymphoma patients in Guangxi and Guangdong provinces of China in the highly active antiretro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
2
0
0
Order By: Relevance
“…Another factor which has been shown to negatively affect DLBCL survival elsewhere is associated oncogenic viral infection, particularly EBV, [38][39][40] hepatitis B (HBV), 41,42 and hepatitis C (HCV). 18,[43][44][45] Here, we showed a hepatitis B seropositivity rate among the PLWH of 11.1%, which is similar to that reported in 2 studies from Nanjing China, 18,22 higher than that reported in Shanghai (7%), 46 and lower than that reported in the USA and in another study from Nanjing (;20%). 45,47 However, HBV seropositivity had no significant impact on survival.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Another factor which has been shown to negatively affect DLBCL survival elsewhere is associated oncogenic viral infection, particularly EBV, [38][39][40] hepatitis B (HBV), 41,42 and hepatitis C (HCV). 18,[43][44][45] Here, we showed a hepatitis B seropositivity rate among the PLWH of 11.1%, which is similar to that reported in 2 studies from Nanjing China, 18,22 higher than that reported in Shanghai (7%), 46 and lower than that reported in the USA and in another study from Nanjing (;20%). 45,47 However, HBV seropositivity had no significant impact on survival.…”
Section: Discussionsupporting
confidence: 88%
“…The frequency of documented extranodal involvement in PLWH was somewhat higher than that reported in one study from the WC of SA (;50%) 9 and another study from the United States of America (USA) (;40%), 11 but comparable to several other reports of HIV-DLBCL from other parts of the world 13,[18][19][20][21][22] at both timepoints (;70%), with involvement of the GIT being the most common extranodal site. Interestingly, extranodal involvement was observed in a similar proportion of HIV negative patients, with the predominant extranodal site being the bone marrow in this group.…”
Section: Discussionsupporting
confidence: 50%